2017
DOI: 10.1016/j.bbr.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious ratings of social touch reflect the anatomical distribution & velocity tuning of C-tactile afferents: A hedonic homunculus?

Abstract: A subclass of C-fibres, C-tactile afferents (CTs), have been discovered which respond preferentially to low force/velocity stroking touch, that is typically perceived as pleasant. Molecular genetic visualization of these low-threshold mechanosensitive C-fibres (CLTMs) in mice revealed a denser distribution in dorsal than ventral thoracic sites, scattered distal limb innervation and a complete absence from glabrous paw skin (Liu et al., 2007). Here we used third-party ratings to examine whether affective respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
63
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 32 publications
22
63
2
Order By: Relevance
“…In a second task, we assessed how participants responded to the mere observation of others being touched, both at CT-optimal (3cm/s) or non-optimal (fast, 30 cm/s; static, 0 cm/s) velocities. Several previous studies have reported that vicarious ratings of moving touch show the same relationship to stroking velocity as directly felt touch (Björnsdotter et al, 2011;Morrison et al, 2011;Walker et al, 2017b). In both tasks, we hypothesized that MDMA, but not MA, would increase perceived pleasantness of touch at the CT-optimal velocity.…”
Section: Introductionmentioning
confidence: 80%
“…In a second task, we assessed how participants responded to the mere observation of others being touched, both at CT-optimal (3cm/s) or non-optimal (fast, 30 cm/s; static, 0 cm/s) velocities. Several previous studies have reported that vicarious ratings of moving touch show the same relationship to stroking velocity as directly felt touch (Björnsdotter et al, 2011;Morrison et al, 2011;Walker et al, 2017b). In both tasks, we hypothesized that MDMA, but not MA, would increase perceived pleasantness of touch at the CT-optimal velocity.…”
Section: Introductionmentioning
confidence: 80%
“…This topic has been under investigation before, but with important limitations. Most importantly, previous studies have almost exclusively focused on one type of simple touch such as brush/hand stroking of the skin ( Blakemore et al., 2005 ; Ebisch et al., 2008 , 2011 ; Morrison et al., 2011 ; Schaefer et al., 2012 ; Walker et al., 2016 ). While these studies probably underestimate the complexity of processes involved in more complex touch interactions, they already showed some very interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, psychologists and neuroscientists have increasingly studied the role of touch in social context, how the emotions were conveyed through touch, and its neural basis [ 4 , 7 ]. Despite of the importance and high frequency of touch communication and increasing interest in this topic, however, stimuli created for these studies poorly represent the actual phenomenon of socio-affective touch, and are mostly limited to video clips showing simple events such as a hand being stroked, slapped or brushed [ 8 15 ]. These studies therefore only address a very small part of "affective touch" since humans use much more complex and varied interactions to express affective intentions (both positive and negative) by touch.…”
Section: Introductionmentioning
confidence: 99%